2013
DOI: 10.1111/chd.12091
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI Correlates with Postnatal CT Angiogram Assessment of Pulmonary Anatomy in Tetralogy of Fallot with Absent Pulmonary Valve

Abstract: In tetralogy of Fallot with absent pulmonary valve, pulmonary stenosis and regurgitation results in significant pulmonary artery dilatation. Branch pulmonary artery dilatation often compresses the tracheobronchial tree, causing fluid trapping in fetal life and air trapping and/or atelectasis after birth. Prenatal diagnosis predicts poor prognosis, which depends on the degree of respiratory insufficiency from airway compromise and lung parenchymal disease after birth. Fetal magnetic resonance imaging (MRI) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Finally, it should also be noted that several of the MRI studies reported in our series concomitantly provided important complementary imaging that could directly or indirectly impact the cardiac prognosis, for example describing the devastating extent of pulmonary compression from a very large diaphragmatic hernia in a fetus that did not survive to term. Fetal MRI can also be used to assess lung parenchymal lesions and airway compromise in CHD and has been used to demonstrate the presence of pulmonary lymphangectasia in a fetus with hypoplastic left heart syndrome, an important prognostic finding . MRI of the fetal brain may provide crucial information to clinicians and parents regarding medium‐term and long‐term prognoses, which may have a profound effect on both prenatal and postnatal management independent of the underlying cardiac diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should also be noted that several of the MRI studies reported in our series concomitantly provided important complementary imaging that could directly or indirectly impact the cardiac prognosis, for example describing the devastating extent of pulmonary compression from a very large diaphragmatic hernia in a fetus that did not survive to term. Fetal MRI can also be used to assess lung parenchymal lesions and airway compromise in CHD and has been used to demonstrate the presence of pulmonary lymphangectasia in a fetus with hypoplastic left heart syndrome, an important prognostic finding . MRI of the fetal brain may provide crucial information to clinicians and parents regarding medium‐term and long‐term prognoses, which may have a profound effect on both prenatal and postnatal management independent of the underlying cardiac diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…87 Several studies have shown that fetal MRI provides information regarding cerebral structural findings and changes in brain metabolism in fetuses with specific CHD that may affect the postnatal prognosis. 74,75,90 In fetuses with HLHS, abnormal lung parenchyma described as "nutmeg lung" was found to be representative of abnormal pulmonary lymphatics 91 ( Figure 10). 74,75,90 In fetuses with HLHS, abnormal lung parenchyma described as "nutmeg lung" was found to be representative of abnormal pulmonary lymphatics 91 ( Figure 10).…”
Section: Fetal Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Dilated lymphatics can be primary, due to abnormal development of the pulmonary lymphatic system or can be secondary to obstruction to pulmonary venous flow due to CHD such as HLHS or TAPVR. 74,75 In addition, fetal MRI has also shown to add important information among the fetuses with cardiac malposition suspected by fetal echocardiography. 90 Tetralogy of Fallot with APV fetuses with significant airway obstruction and congenital lobar emphysema is at increased risk of severe hypoxia at birth 71 ( Figure 11).…”
Section: Fetal Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 2 more Smart Citations